If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 = 6x + 3 Reorder the terms: -3 + x = 6x + 3 Reorder the terms: -3 + x = 3 + 6x Solving -3 + x = 3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3 + x + -6x = 3 + 6x + -6x Combine like terms: x + -6x = -5x -3 + -5x = 3 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 + -5x = 3 + 0 -3 + -5x = 3 Add '3' to each side of the equation. -3 + 3 + -5x = 3 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 3 + 3 -5x = 3 + 3 Combine like terms: 3 + 3 = 6 -5x = 6 Divide each side by '-5'. x = -1.2 Simplifying x = -1.2
| 8(2-x)-12=-3x | | x-6=6x+3 | | v-6=5 | | -5x(x-1)(3x+2)=0 | | 7x+3-4x=-6 | | 4-6w=3 | | -3z-7=8 | | 2(x+3)-x=10 | | 4(-1)-9(-1)+22=3(-1)+30 | | 3x^4+2x^3-14x^2+108x+13=0 | | -3m^2+27=0 | | 3(x-5)-14=2(x-7)+4 | | 3y-2=4 | | x/9=5 | | 3x(x+12)=0 | | 12a=-a^2 | | 4p^2-16=0 | | 18x^2-3x-6= | | 5(ln(3x))=14 | | x-6x^2=0 | | 0.3(x+40)+0.3x=21 | | a^2+2a=15 | | -2(3s-2)-4=-3(4s+3)-4 | | 6m^2-36m=0 | | 3v-8=19 | | 3(x+7)=3x+21 | | -12x+9=-6x-18 | | 1000(6x-10)=40(495+100x) | | 5(x-1)=-2x+37 | | 10+2= | | 3v-8=10 | | -((x+5)+5x+2)=(8x+6) |